English songs to enhance listening skills in the 1st semester of PINE major students - Velez Parrales, Luis Ariel (2024)
This study analyzes the use of English songs to enhance listening skills in first-semester PINE (Pedagogy of National and Foreign Languages) major students. The research addresses the need for innovative approaches in teaching listening skills, which is crucial for global communication. In Ecuador, where English proficiency is essential, traditional methods have fallen short. The focus is on first-semester PINE students, future educators shaping language skills. Utilizing a qualitative approach, specifically phenomenological studies, this research applied focus groups and questionnaires. Findings reveal students regularly use English songs for listening skills improvement. Techniques like subtitle reading and repetition contribute to effective skill development. Students prefer songs over traditional methods due to their enjoyable and efficient approach.